Systematic review of the literature associated with agribusiness [Revisión sistematica de literatura asociada a los agronegocios] (2016)
"In recent years, increased research and studies on agribusiness has been evident, as the effort to give explanation to the development of agribusiness companies and the demands required by today's markets sector. Therefore, this paper aims to conduct a review of literature associated with agribusiness as a result of the research project ""knowledge management in agribusiness binational (Peru-Colombia): construction of teaching cases for business schools ""; which identified trends in major publications and authors on the subject of management in agribusiness, from the search for the following key words ""agribusiness and knowledge management"", ""agribusiness and organizational management"", ""agribusiness and models of agribusiness"" and finally ""agribusiness and economy development""; the latter combination of keywords is to identify the importance of developments in the current issue of emerging economies in the world. In this article the authors with the highest citation, the important journals and more countries identify publications, while the main theoretical research findings. For this, a search for the items that are in the SCOPUS database and are published in journals belonging to the SJR (Scimago Journal and Country Rank) was performed. The main results of the study indicate that research and publications that have been made are focused on explaining patterns of agribusiness and the trend of these studies is increasing, with regard to other issues of management and administration, where potential is identified for further research. © 2016 Revista ESPACIOS."